Pengaruh Pemberian Variasi Dosis Pupuk Kandang Terhadap Pertumbuhan Tanaman Mahkota Dewa (Phaleria macrocarpa (Scheff.) Boerl.) - Nur Anggraeni, Dewi (Jurusan Biologi UIN Alauddin Makassar, 2014)
Research on the effect of dose variations of manure on Godâs Crown (Phaleria macrocarpaÂ (Scheff.) Boerl.) growth was implemented in Ambarketawang, Gamping, Sleman, Yogyakarta. ThisÂ study aimed to determine the effect of administration of dose variations of manure on Godâs CrownÂ growth. This research method using a complete randomized design (CRD) with one treatment factorsÂ which is administrating manure into polybags containing 2 kg of soil with dose variations of 0 g, 50Â g, 100 g, 150 g, 200 g, and 250 g. The parameters measured in this study are height, leaf number, andÂ fresh weight of Crownâs God plant. The results were analyzed by analysis of variance (ANOVA), ifthe data is meaningful (significant difference) then followed by LSD test level of 5%. The resultsÂ obtained are the effects of administration of manure dose variation produce different Crownâs GodÂ (Phaleria macrocarpa (Scheff.) Boerl.) growth, and the best dose for Crownâs God (PhaleriaÂ macrocarpa (Scheff.) Boerl .) growth is 250 grams.Keywords: crownâs god (Phaleria macrocarpa (Scheff.) Boerl.), dose of manure